ENVIRONMENTAL PROTECTION: MODERN PROBLEMS AND EFFECTIVE SOLUTIONS - Akramova Dilbar Doniyor qizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This paper examines the growing environmental challenges faced by the modern world, including climate change, pollution, and resource depletion. It emphasizes the role of human activity in environmental degradation and highlights practical solutions such as sustainable development, green energy, and environmental education. The study concludes that joint efforts are essential to preserve the planet for future generations.